Penggunaan Instagram oleh Salon Mobil Topcaredetailing untuk Tujuan Promosi - Trisya Fajrin; Salman Naning (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2023)
This study aims to find out the content of the Topcare detailing Instagram account in attracting consumers or customers who visit and to find out how to take videos and photos at the Topcare detailing car salon business to attract customers' attention. In this study, researchers used the theory of diffusion of innovation, a qualitative approach. Data collection techniques using semi-structured interviews. The data analysis technique used qualitative analysis. The results show that the use of Instagram by Topcare detailing car salons for promotional purposes is considered effective because it can increase turnover every month. The research obtained is in accordance with the view of the theory of diffusion of innovation. The form of Topcare detailing's Instagram account content in attracting visiting consumers or customers is an innovation where media language plays an important role in organizing or making Topcare detailing exist in order to influence customers.